EVALUASI PROGRAM PENGAWAS SMA NEGERI DI KOTA MAKASSAR - Zainal, Zainal (PEP Educational Assessment, 2017)
This study aims to determine the components of supervisory SMA program in Makassar consisting of: 1) Component inputs (antecedents); 2) The components of the process (transactionts); 3) Components of results (output). This study is the evaluation by using Stake's Countenance Model, subjects in this study is a school superintendent, coordinator of school supervisors, principals and teachers. Selection of informants in this study conducted by purposive sampling. Data was analyzed using descriptive and qualitative analysis through three grooves. Conclusion of the Program Supervisor Senior High School in the city of Makassar as follows: 1) Component inputs (antecedents), namely: (a) recruitment / appointment and administrative requirements of the supervisor High School, head of SMA is not yet fully meet the evaluation criteria, (b) subject teachers in SMA has been fully qualified S-1 but still there are teachers who do not teach according to the educational background of the S-1; 2) The components of the process (transactionts), namely: (a) control of a school supervisor in preparing the planning administration supervision is maximum, (b) the implementation of the supervision of the managerial to the principal adequate, but the implementation of academic supervision is considered inadequate, (c) the interaction between the Supervisory school principals well established, while the interaction between the school superintendent with the subject teachers in schools have not been well established; 3) components results (output), namely: (a) the effectiveness of managerial principals in the preparation of school programs and implement the eight National Education Standards still needs to be improved, (b) the effectiveness of managerial principals in the implementation of school programs are good, (c) increase the capacity subject teachers in preparing lesson plans and PBM implementation is still low.